The Safety Showdown: Perceptions and Practice Change of Inpatient Caregivers After a Patient Safety Escape Room. Issue 3 (12th May 2023) - Daniels, Darami A.; Caruso, Stephanie; Morrell, Briyana; Eukel, Heidi N.
Abstract : Educational escape rooms actively engage learners and foster teamwork. It is unclear if they result in nursing practice change. Three hundred ninety-eight nursing and ancillary caregivers participated in an escape room involving patient safety and fall prevention concepts. An average rating of 4.3 out of 5 on the escape room perception scale was obtained via a postsurvey, showing positive perceptions of the event. In a delayed postsurvey, participants discussed resultant patient safety practice changes.